Analysis The Suitability Of Arabic Learning Videos On Youtube Based On The Gagne Model - Resti, Amanda; Asep Sopian (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to analyze the extent to which Arabic learning videos available on YouTube adhere to Gagne’s Nine Events of Instruction. The research employs a qualitative descriptive method with content analysis as the primary approach. A total of ten Arabic instructional videos were purposively selected and evaluated based on the presence of each of Gagne’s instructional steps. The results show that only two out of ten videos fulfilled more than six of Gagne’s stages, while the rest met only three to five stages. The most frequently observed stages were “presenting the stimulus” and “providing feedback,” whereas key initial stages such as “gaining attention” and “informing learners of objectives” were frequently omitted. These findings suggest that most Arabic learning videos lack a structured instructional design, which may impact the effectiveness of learning. The study highlights the importance of incorporating a comprehensive instructional framework when designing educational content, particularly for language acquisition. It also emphasizes the need for content creators to be trained in instructional design principles. This research recommends the development of more pedagogically sound learning videos that fully implement Gagne’s model to enhance the quality of digital Arabic language instruction.